Committee on Multi-Media Instruction in Accounting. (The Accounting Review, 1972)
The article highlights the report of the Committee on Multi-Media Instruction in Accounting of the American Accounting Association. The charge to this committee is to study and prepare a report upon current and potential uses of various instructional media and systems in accounting education, including suggestions and recommendations relative to their use by accounting educators. The emphasis in the charge on uses of various instructional media and systems– both current and potential–required the Committee to be concerned with ends as well as means. There are various predictions as to the result of the meeting of technology and education. On the basis of the limited responses, the Committee is hesitant to draw inferences on the use of programmed textbooks in the whole field of accounting education. In addition to learning theories, there are theories of communication which have consequence to the learning process. Several economic theories are pertinent to the learning, especially utility theory and information economics. Training methods in which the trainer is attempting to aid participants in their own efforts to understand group dynamics and to acquire interpersonal skills in various situations.